Application of Early Childhood Development Stimulation in Families with Working Mothers - Jafar, Eka Sufartianinsih; Ansar, Wilda (Polteknik Ilmu Pemasyarakatan, 2024)
Stimulation is very important in early childhood development so that children's abilities develop optimally according to their age. The aim of the research is to determine the application of developmental stimulation from all aspects of development starting from physical, motoric, language, social and emotional aspects carried out by families with working mothers while accompanying early childhood children aged 0-5 years at home. This type of research is descriptive qualitative research with the research subjects being parents who have children aged 0-5 years in Makassar City. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction collection, drawing conclusions and presenting data. The results of this research show that the application of developmental stimulation to working mothers prioritizes stimulating aspects of children's cognitive, social and fine motor development compared to other developmental aspects such as language, emotions, morals and religiosity. Working mothers are generally supported by other caregiver figures, the majority of whom come from the family, such as husbands, grandparents, aunts, older siblings as well as caregivers outside the family and day care. There are several factors that influence the developmental stimulation provided by working mothers, namely employment, duration of work, number of children, marital status, and knowledge about developmental stimulation and child care. The contribution of this research is expected to encourage awareness among all family members, especially working mothers and other caregivers, of the obligation to educate children and the importance of stimulating development so that young children are able to achieve developmental tasks appropriate to their age.